2018
DOI: 10.1099/ijsem.0.003009
|View full text |Cite
|
Sign up to set email alerts
|

Ottowia konkukae sp. nov., isolated from rotten biji (tofu residue)

Abstract: A Gram-negative, aerobic, non-motile, non-spore-forming and rod-shaped bacterial strain, designated SK3863, was isolated from rotten biji (residue remaining after making tofu). This bacterium was characterized in order to determine its taxonomic position by using the polyphasic approach. Strain SK3863 grew well at 25-37 °C on Reasoner's 2A agar plates. On the basis of 16S rRNA gene sequence similarity, strain SK3863 belonged to the family Comamonadaceae and was related to Ottowia beijingensis GCS-AN-3 (96.5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
2
8
0
Order By: Relevance
“…The DNA G+C content fall within the range from 59.0 to 68.5 mol% [10]. At the time of writing, the genus Ottowia comprises seven identified species with validly published names [9][10][11][12][13][14][15]. Samples were collected from various environments, including activated sludge, rice beverage, fish intestines and tofu residue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The DNA G+C content fall within the range from 59.0 to 68.5 mol% [10]. At the time of writing, the genus Ottowia comprises seven identified species with validly published names [9][10][11][12][13][14][15]. Samples were collected from various environments, including activated sludge, rice beverage, fish intestines and tofu residue.…”
Section: Introductionmentioning
confidence: 99%
“…Common characteristics (Gram-stain-negative, non-motile, non-spore-forming, rod-shaped, catalase- and oxidase-positive) are shared by the members of the genus Ottowia [11]. Ubiquinone 8 (Q-8) and C 16 : 0 , summed feature 3 (C 16 : 1 ω 7 c and/or C 16 : 1 ω 6 c ) and summed feature 8 (C 18 : 1 ω 7 c and/or C 18 : 1 ω 6 c ) are the major quinone and major fatty acids, respectively [12]. The DNA G+C content fall within the range from 59.0 to 68.5 mol% [10].…”
Section: Introductionmentioning
confidence: 99%
“…It was not detected in any background technical controls. Ottowia is a genus of bacteria that has been isolated from industrial and municipal wastewater (9699), sikhye (100), tofu residue (101), and fish intestines (102); it has not been identified in investigations of the human uterus. Nevertheless, Ottowia is a member of the family Comamonadaceae, and Chen et al (23) and Winters et al (30) reported that Comamonadaceae was among the most relatively abundant bacterial taxa in the human endometrium.…”
Section: Discussionmentioning
confidence: 99%
“…This species was named Ottowia thiooxidans . Meanwhile, six additional species of the genus and one species without a validated name have been proposed, namely Ottowia beijingensis [2], Ottowia caeni [3], Ottowia flava [4], Ottowia konkukae [5], Ottowia oryzae [6], Ottowia pentelensis [7] and ‘ Ottowia shaoguanensis ’ [8]. The genus Ottowia is classified within the family Comamonadaceae and the phylum Betaproteobacteria .…”
Section: Full-textmentioning
confidence: 99%
“…Data for strain 1 from this study; data for strains 2 and 3 from Shi et al[3], obtained with identical methods and precultivation conditions. Data for strains 2 (in brackets), 4, 5 and 7 were obtained by Heo et al[5]; data for strain 6 from Yi et al[4]. tr, trace amounts (<0.5 %).…”
mentioning
confidence: 99%